Clean Water Infrastructure Provision Strategy to Support the Industrial Sector in Indramayu Regency in Supporting the Rebana Area - Afifah, Nur Zahrah; Putri Abdi, Azizah; Izzah Ajrina, Fadiah (Universitas Sulawesi Barat, 2025)
Clean water infrastructure is essential for supporting the Rebana Industrial Area in Indramayu, where high industrial demand risks conflict with the crucial agricultural sector and exacerbates an existing water crisis. This study aims to develop an integrated strategy to boost water supply and service quality in Indramayu. Using a mixed method approach combining quantitative water balance (demand-supply) and qualitative SWOT analysis the main findings reveal a significant water deficit. The current supply of 79.448 l/sec fails to meet the demand of 157.740,7 l/sec, resulting in a −78.292,7 l/sec deficit in 2025, projected to remain −49.438,1 l/sec by 2045. Adding to the crisis, raw water quality in the two main rivers is classified as moderately to heavily polluted. The main conclusion emphasizes the urgent need for supply interventions. The recommended strategy focuses on two pillars: increasing raw water quantity by utilizing 3.600 l/sec from regional alternative sources and enhancing local reservoir capacity to enforce the groundwater ban, and improving services through the construction of new, high-tech Water Treatment Plants (WTPs) and expanding piping networks. This study provides vital policy recommendations for the local government to ensure sustainable water access and industrial growth in the Rebana Region.